2006
DOI: 10.1111/j.1600-0501.2005.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early telescope loading of non‐submerged ITI implants in irradiated and non‐irradiated oral cancer patients

Abstract: The results suggest reliable non-submerged implantation and early loading. However, bone loss in irradiated mandibles, combined with higher average Periotest values and gingival recession in an oral environment of altered saliva quantity, quality, microflora and local scarring, requires extended follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 29 publications
0
55
1
Order By: Relevance
“…For example, Heberer et al (2011) and Landes and Kovacs (2006) reported high survival rates for SLA, SLActive, and TPS implants. It would be interesting to group the machined versus textured implants and analyze the differences between them (the results and conclusions might be different from those reported herein).…”
Section: Quality Of the Evidence And Potential Biases In The Review Pmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Heberer et al (2011) and Landes and Kovacs (2006) reported high survival rates for SLA, SLActive, and TPS implants. It would be interesting to group the machined versus textured implants and analyze the differences between them (the results and conclusions might be different from those reported herein).…”
Section: Quality Of the Evidence And Potential Biases In The Review Pmentioning
confidence: 99%
“…The findings regarding the domains of the modified Newcastle-Ottawa scale were as follows: 1: none of the studies reported sample size calculations; 2 and 3: in all of the studies, the representativeness of the irradiated and nonirradiated (when described) patients was considered to be adequately addressed; 4: assessment of peri-implant conditions was considered adequate in 8 studies (Albrektsson et al, 1988;Andersson et al, 1998;Brogniez et al, 1998;Esser et al, 1999;Granstrom et al, 1999;Goto et al, 2002;Visch et al, 2002;Landes and Kovacs, 2006) and unclear for the remaining articles; 5: only Albrektsson et al (1988) and Granstrom et al (1999) did not describe whether radiotherapy was performed before or after implant placement; 6: none of the studies reported training or calibration of the examiners of clinical outcome; 7: 2 studies had a prospective design (Visch et al, 2002;Landes and Kovacs, 2006); 8: 2 studies reported that all patients received similar implant therapy (Esser et al, 1999;Schepers et al, 2006); 9: 1 publication described statistical assessment performed with control for confounders (Visch et al, 2002); 10: none of the authors described whether independent blind assessment of peri-implant conditions was used; An approximate number of implants was calculated based on the survival rate (%), as well only data from implants placed in residual bone were extracted from the study. Goto et al 11: all of the studies described the radiation doses used for oncologic treatment, except for Albrektsson et al (1988); 12: in 2 publications, > 70% of the treated patients were followed during the entire study period (Landes and Kovacs, 2006;Katsoulis et al, 2013); 13: Esser et al (1999), Granstrom et al (1999), Schepers et al (2006), Werkmeister et al (1999), Goto et al (2002) and Visch et al (2002) compared their outcomes using statistical analyses; and 14: all authors defined the number of patients and/or implants per group as the unit of analysis.…”
Section: Risk Of Bias In the Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies involving implants placed in adult patients who have received radiotherapy reported lower success rates [ 44 ], but there are also several clinical studies demonstrating that dental implants can osseointegrate and remain functionally stable in patients who had received radiotherapy [ 45 ]. Other authors have reported successful dental implant outcomes but occurrence of late complications, such as bone loss and mucosal recession, possibly due to altered saliva flow and increased bacterial colonization [ 46 ]. Several case-control studies have shown evidence of improved outcomes in patients with history of radiotherapy and dental implants with the addition of hyperbaric oxygen therapy mainly through reduction in the occurrence of osteoradionecrosis and failing implants [ 47 ].…”
Section: Dmentioning
confidence: 99%